A CFD study: Influence of biofouling on a full-scale submarine. (April 2021) - Uzun, Dogancan; Sezen, Savas; Ozyurt, Refik; Atlar, Mehmet; Turan, Osman
Abstract: The aim of this study is to investigate the effect of biofouling related hull roughness on a full-scale submarine by taking into consideration the resistance components, effective power, and nominal wakefield using a Computational Fluid Dynamics (CFD) solver. The validation study was first performed for the model scale submarine form in hydraulically smooth (reference) condition with the available experimental data. Following that, roughness functions, representing the different biofouling conditions, were obtained from the literature and then employed in the wall function of a RANS solver. Later on, the full-scale submarine form was investigated both in the smooth and different grades of biofouling related roughness conditions. The scale effects were examined between the model and full-scale submarine forms through the total resistance components and nominal wake fraction in the smooth reference condition. In rough cases, the frictional resistance values of the full-scale submarine form obtained by RANS solver were compared with those of predicted using Granville`s similarity law analysis based on the flat plate approach. The numerical results showed that the roughness causes a substantial increase in effective power, ranging from ∼36% to ∼112% depending on the roughness height and submarine speed. Furthermore, with an increasing boundary layer thickness (due to the impact of increasing roughness heights), the mean nominal wake fraction values increase ranging from ∼25% to ∼68 compared to the reference wake fraction values in the axial direction at the stern.